Rechallenge with dabrafenib plus trametinib in anaplastic thyroid cancer: A case report and review of literature - ATASOY, BESTE MELEK; ÖZGÜVEN, SALİH (MOSBY-ELSEVIER, 2021)
Introduction: Anaplastic thyroid carcinoma (ATC) is a highly aggressive, undifferentiated rare tumor. Median overall survival is usually between 8 and10 months, with a 1-year survival rate of 20%. Conventional anthracycline based chemotherapy regimens demonstrate low response rates with short duration. Novel therapeutic agents including BRAF and MEK inhibitors based on the molecular landscape of ATC have been investigated. Case presentation: We herein report the rechallenge of a 52-year-old ATC patient with BRAF V600E mutation with dabrafenib plus trametinib. She presented with recurrent and progressive disease despite surgery, radiation therapy, 3 different chemotherapy regimens, and combination of dabrafenib-trametinib in different settings. She was rechallenged with dabrafenib-trametinib, and had a good response. Conclusion: To our knowledge, this is the first ATC case who responded to dabrafenib-trametinib rechallenge, reported in the literature. We want to emphasize that combination of dabrafenib and trametinib might be a good choice for resistant locoregional and metastatic ATC patients with BRAF V600E mutation, particularly in whom rapid clinical response is urgently needed. Moreover, rechallenge with this combination should be kept in mind in selected cases. (c) 2020 Elsevier Inc. All rights reserved.
Keywords: Anaplastic thyroid carcinoma; BRAF V600E; Dabrafenib and trametinib; Rechallenge